Drivers of sustainable practices in a developing country’s garment and textile industry: The role of sustainability challenges, limited material access, and economic constraints - Kweku Safo-Ankama; Lord Emmanuel Yamoah; Naa Omai Sawyerr; John Amoah (PLoS ONE, 2026)
Sustainable practices in small and medium-sized enterprises (SMEs) are critical for environmental resilience and economic viability, particularly in developing economies like Ghana’s garment and textile sector. This study investigates the drivers of sustainable practices among SME drivers in the Western Region of Ghana, focusing on sustainability challenges, limited access to materials, and economic constraints. Employing a quantitative approach, data were gathered from textile and garment SMEs via simple random sampling through an online and offline approach. Partial Least Square Structural Equation Modelling (PLS-SEM 4.0) was used in processing and analysing the 315 valid responses gathered. Findings revealed that sustainability challenges and limited material access have a significant effect, while economic constraints have an insignificant effect. These results underscore the need for targeted interventions, including investments in recycling technology and stakeholder collaboration. The study contributes to SME sustainability literature in developing contexts and offers practical recommendations to foster eco-friendly production, job creation, and regional leadership in West African textile manufacturing.